(untitled) (Balneo and PRM Research Journal, 2024)
: Background: For knee osteoarthritis (OA) pathogeny, cartilage damage is important, and ultrasonography (US) is helpful in assessing specific joint issues. Objectives: We intend to find correlations between functionality, pain level, serum glucose, cholesterol, triglycer-ides, uric acid, systemic inflammation and US findings for patients with knee OA. Meth-ods: For 50 consecutive subjects with symptomatic bilateral knee OA staged according to the scale Kellgren-Laurence(K-L) noted anamnestic data, Body Mass Index (BMI), func-tionality evaluated by Western Ontario and McMaster University Osteoarthritis Index (WOMAC) and pain’ intensity through Visual Analogue Scale (VAS). Using the US, the cartilage, meniscal and tendon changes, osteophytes, and fluid collections were assessed for 100 knee joints. SPSS 29.0.2.0 was used for statistical analysis. Results: In our group, with an average age of 60.54 years, there was observed a weak direct correlation between WOMAC and K-L grading (r=0.34) and a negative correlation between BMI and the carti-lage size on the external femoral condyle (r=-0.28). Its thickness on this site was directly correlated with lateral osteophyte severity. Smokers’ injuries on the intercondylar groove were increased. Conclusion: Lateral femoral condyle cartilage thickness is inversely asso-ciated with BMI, and K-L grading directly correlates with dysfunctionality. The smokers had higher intercondylar cartilage injuries.